Transmission ratio distortion at the growth hormone gene (GH1) in bovine preimplantation embryos: An in vitro culture-induced phenomenon? - Murphy, Angela M.; Meade, Kieran G.; Hayes, Patricia A.; Park, Stephen D.E.; Evans, Alex C.O.; Lonergan, Patrick; MacHugh, David E. (Molecular reproduction and development, 2008)
The growth hormone gene (GH1) and its polypeptide product (GH) have a crucial role in reproduction, embryogenesis and general development. A polymorphism present in the fifth exon of the bovine GH1 gene (GH1 p.Leu127Val) has been associated with GH release and milk production in cattle. The objective of the present study was to examine the genotype frequencies of the GH1 p.Leu127Val polymorphism in bovine blastocysts produced in vitro and in vivo to determine if allelic variation of the GH1 gene affects embryo development and survival. A heterozygous (p.Leu127/Val127) sire was used for in vitro fertilization of oocytes of unknown maternal genotype (n = 104) and known maternal genotype (n = 115). PCR amplification and genotyping of the GH1 gene from Day 8 blastocysts derived from these fertilized oocytes demonstrated that there was significant over‐representation from the expected Mendelian ratio of GH1 p.Leu127/Leu127 homozygotes from oocytes of known maternal genotype (P = 0.006). Contrary to this, analysis of in vivo‐produced bovine blastocysts of known parental GH1 genotype (n = 69) did not reveal an overrepresentation of GH1 p.Leu127/Leu127 homozygotes. These results suggest that developing in vitro‐produced embryos are exposed to a selection process, probably due to a less favorable culture environment, that acts to increase the number of GH1 p.Leu127/Leu127 homozygotes, thereby giving rise to the observed transmission ratio distortion (TRD) of GH1 genotypes when compared to in vivo produced embryos. Mol. Reprod. Dev. 75: 715–722, 2008. © 2007 Wiley‐Liss, Inc.